O processo de tomada de decisão do capital empreendedor e o financiamento de empresas de base de inovação tecnológica - Miranda de Sousa, Sergio Henrique (2006)
The Venture Capital and Private Equity (VC/PE) are alternatives source of financial resources to the enterprises that need investments. The research analyzes the characteristics from the invested companies and the requirements imposed by the investors of VC/PE to choose the companies to invest in which occur the capital contribution. The methodological procedures involve the a critic literature about the theme and a research based in interviews in eight funds and twelve answered questionnaires, to identify and to analyze the routines and procedures involved in the selection of the investments of Brazilian risk funds. Through the research bibliographical it can be verified that the national scenery of VC/PE industry demonstrates empowerment and development mainly after 2000, there are new investors' attraction and lack of legislation motivate. The results of the field research allowed to identify the requirements that the enterprises of base of technological innovation need to fill out to capture financial resources, they are the same that the one of the other companies and the interviews showed a preference of 62,5% in contribution in enterprise of this type. The criteria of the investments vehicles selection and the routines are several, and besides the data financiers, several other attributes of the companies are analytically studied as well as the entrepreneur and him team, so there is the smallest possible risk in the choice of the company invested with high future profitability. The rigorous selection criterion allows to choose the enterprises that present better return possibilities, with a level of acceptable risk. This option of financial resources also aggregates professionalism to the invested company, it demonstrates to have benefits and to be a promoter to the entrepreneurship. However, VC/PE is not solution for all the financial needs or for any company, it represents a very small portion of resources for the financing of the investments of the firms and given the existence the asymmetry of information and uncertainty of the results, the proposed routines don't guarantee 100%, although they assure a considerable medium return to the venture capitalist, given the diversified portfolio.